Evaluation of Program Evaluation and Review Technique (PERT) for project management using Monte Carlo Simulation. - Lim, Soon Chung. (2008)
This study was done to investigate the criticisms that PERT has received from researchers. The assumptions made in the procedures seem to cause the inaccurate results that users often get. A number of modifications have been made to the original procedure, resulting in methods like PNET. These circumvent the inherent deficiencies in the original method and give more accurate results. It is also possible to employ Monte Carlo simulation as an alternative to the original PERT method.